Buffer overflow asymptotics for multiplexed regulated traffic - Ying, Y.; Guillemin, F.; Mazumdar, R.; Rosenberg, C. (Performance evaluation, 2008)
By characterizing the worst-case profile, which maximizes the content of a buffer fed with leaky bucket regulated flows in packet telecommunication networks, we derive a tight upper bound in the many-sources regime for the tail distribution of the workload generated by these flows in a FIFO queue with constant service rate. Furthermore, we compare this workload distribution with an M / G / 1 queue and get insights on the better-than-Poisson property of regulated flows. We conclude that the superposition of independent regulated flows generates an asymptotically smaller workload than a marked Poisson process whose service times and intensity depend on the parameters of regulated sources.